Compression strength of metal-ceramic fixed dental prostheses reinforced by nanoparticle silica from rice husks - Sinamo, Sopan (2024)
Fracture occurred in metal-ceramic Fixed Dental Prostheses (FDPs) after being permanently cemented has been major concern in dentistry. This study aims to evaluate the compression strength on metal-ceramic samples via the addition of nanoparticle silica (NPS) to opaque porcelain layers. Silica was synthesized via sol-gel method and sonicated for 270 minutes. The morphological and chemical characteristics of the silica were observed using SEM, TEM and XRF analysis. The NPS powder was mixed into the commercial opaque-porcelain powder with variation of 0.5; 1; 1.5; 2; 2.5; 3 wt % and as a control. Co-Cr bimetals prepared in 28 samples were used in the study divided into seven groups (n=4 each). The veneering of opaque-porcelain-NPS and commercial dentine on metals was sintered at 920-950°C. All specimens were tested for the compression strength using a universal testing machine. The XRF analysis confirmed the presence of silica, SEM and TEM showed amorphous NPS with spherical and agglomerated to form clusters. There was a statistically significant difference of compression strength among samples, and the most significant improvements was in 0.5 wt% addition (p<0.05). Nanoparticle silica synthesized from rice husks via combination of sonication/sol-gel method in a small percentage would improve compression on the metal-ceramic samples.